Goodwill measuring value creation of acquisitions: an empirical research - M.P. Lycklama à Nijeholt; Yolanda K. Grift (Utrecht University, Utrecht School of Economics, Tjalling C. Koopmans Research Institute, 2012)
The reason for this research is that at the beginning of the 21st century, some important changes were introduced in the international standards of accounting affecting reporting on goodwill. The intentions of the standard-setting bodies in drafting the new rules were that the financial statements would better reflect the underlying economics of the acquired goodwill.1 In this research it is tested whether goodwill under the new accounting regime does reflect underlying economics and therefore provides information on expected value creation of the acquisition. The results of the research show that goodwill contains elements of value creation: characteristics of valuecreating acquisitions have a positive effect on purchased goodwill. However, also other characteristics determine the amount of purchased goodwill.
Keywords: 330; Goodwill; Mergers and Acquisitions; SFAS 141; SFAS 142; Value Creation